Social representations of mental ill‑health: A qualitative study with Mental Health Professionals - Martins, António (2017)
The aim of this work is to study the social representations of Psychiatrists, Psychiatrist Interns, Child Psychiatrists and Clinical Psychologists about mental health and mental illness. A qualitative and exploratory study was developed based epistemologically on social constructionism and theoretically on social representations. Through the course of the research 30 health professionals participated in a semi‑structured interview whose content was analysed by means of the NVivo 10 Programme. The results showed that the social representations of mental illness are heterogeneous, emphasizing operational,etiologic‑explanatory and relativist conceptions. Mental health is conceptualized by health professionals according to the flexibility, adaptation, functionality and the biopsychosocial well‑being of individuals. Implications of this study to the theoretical framework of social representations of mental health/illness are considered.